Untangling creativity and art for policy purposes: ethnographic insights on Manchester International Festival and Manchester Day Parade. Issue 2 (4th March 2018) - Symons, Jessica
Abstract : This paper draws on anthropological fieldwork of a civic parade in Manchester from 2010 to 2012 to argue for engaging with creativity as a process rather than an attribute of a particular sector or individual. It shows how the focus on funding and supporting 'creative industries' defined as 'cinema, television, music, literature, performing arts, heritage and related areas' actually excludes and diminishes the potential for others to engage with ideas and creative processes. Two major events in Manchester's cultural calendar – Procession by artist Jeremy Deller, produced by Manchester International Festival and Manchester Day Parade, a council-led civic celebration – both combined community groups with artist input to put large-scale structures and people on the city's streets. In this ethnographic analysis, I argue that the 'creativity' sought from these artists is their adaptive and productive approach to making ideas tangible. By focusing on creativity as a process rather than a character trait, there is even greater potential for stimulating a 'creative' city.